Managing the complexity of digital transformation—How multiple concurrent initiatives foster hybrid ambidexterity - Jan Jöhnk; Philipp Ollig; Patrick Rövekamp; Severin Oesterle (Electronic Markets, 2022)
Incumbent companies are launching digital transformation initiatives (DTIs) to cope with technological changes, challenging competitive environments, increasing customer demands, and other digitalization challenges. The DTI spectrum is broad and covers structural and contextual changes. Companies often launch multiple.~concurrent DTIs, resulting in considerable organizational complexity. However, there has been very little research into the successful management of the interplay between DTIs. Drawing on five management aspects (strategic alignment, governance, methods/IT, people, and culture) and insights from three case companies, we elucidate DTIs' interplay, illustrating that beneficial DTI interplay management leads to a complementary duality instead of a competing dualism in organizational ambidexterity. We explicate that multiple concurrent DTIs can foster structural and contextual ambidexterity, which leads to hybrid ambidexterity, concluding that contextual ambidexterity coheres and balances exploration and exploitation efforts. Thereby, we contribute to a better understanding of DTIs, their interplay management, and their roles to foster hybrid ambidexterity.
Keywords: M15; 620; Digital transformation; Ambidexterity; Hybrid ambidexterity; IT management